Penentuan Indeks Kualitas Tanah Agroforestri Berdasarkan Sifat Kimia Tanah di Sub-DAS Bengawan Solo Hulu Wonogiri - Nur Machfiroh; Supriyadi Supriyadi; Sri Hartati (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
Title : Determination of Soil Quality Index Based on Soil Chemical Properties at The Upstream of Bengawan Solo River Basin Wonogiri. Land conversion extended to the upper of the watershed for residential and agricultural so soil’s ability is decreased to support the soil quality. To solve these problems, in the region upstream of Bengawan Solo, enforced by Agroforestry plantings. Research carried out at the upstream of Bengawan Solo Wonogiri and Laboratory of Chemistry and Fertility of Soil Faculty of Agriculture, Sebelas Maret University Surakarta, in June 2013 until March 2014. Research used a survey method by descriptive and exploratory. Determination of the location of the site sample is done by a stratified random sampling based onland map unit. Sampling was done by a purposive sampling method. The soil quality index is determined by summing the scores for each variable which has selected from Principal Component Analysis (PCA), and then it multiplied by the weight index. The result of the study show that the soil quality of Agroforestry in the upstream of Bengawan Solo Wonogiri based on the chemical properties of the soil is low. The value of soil quality index in the secondary forest is 2.6. While in the Agrosilvopastoral is 2.3 and in the Agrisilviculture is 2.1, which are lower than the secondary forest. Whereas in the Silvopastoral is 3.0, which is higher than the secondary forest.